Growth, mortality and yield of Sarotherodon melanotheron melanotheron (Rüppell, 1852) in the Lake Nokoué and Porto-Novo Lagoon complex Benin, West Africa - LEDEROUN, DJIMAN; Amoussou, Gildas; Baglo, Imaculé S.; Adjibogoun, Hermann; Vodougnon, Hamil; MOREAU, Jacques; LALEYE, PHILIPPE A. (My University, 2020)
The study evaluated some population parameters of Sarotherodon melanotheron melanotheron within a lagoon complex in southern Benin: Lake Nokoué and Porto-Novo Lagoon. Data on the total length, total weight, and sex were recorded monthly between January and December 2015 for 1,745 specimens captured by local fishermen. The asymptotic length L∞ was estimated at 24.68 cm. The growth rate K was 0.86. The total, natural, and fishing mortalities were estimated at 2.46, 1.71, and 0.75 y1, respectively. The size at first sexual maturity was 8.9 and 9.2 cm, respectively, for males andfemales. The size at first capture was estimated at 9.2 cm, which indicates that fish spawn at least once before capture. The current exploitation rate of 0.31 remains below the maximum exploitation rate Emax which was 0.604 but was equal to the exploitation rate retaining 50% of the biomass of the stock (E0.5 = 0.324). This suggests that the stock of S. m. melanotheron is not overexploited in the complex. However, it is recommended that the actual rate of exploitation be kept as it is to ensure a sustainable management of these fish populations.
Keywords: Cichlid / ELEFAN / Lagoon fisheries / Ouémé river / Demographic parameters